UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MENGGUNAKAN MEDIA TEKA-TEKI SILANG DENGAN MODEL PEMBELAJARAN TALKING STICK POKOK BAHASAN EKOSISTEM KELAS VII SMPN 1 KARTOHARJO - Candra Puspitasari; Joko Widiyanto (UNIVERSITAS PGRI MADIUN, 2016)
The purpose of the study was to determine the activity and student achievement on thematerial using instructional media ecosystem crossword puzzle with Talking Stick models. This research is a classroom action research (CAR) conducted at SMP Negeri 1 Kartoharjo, with theobject of research students VIIE class with 15 students. Data collection is done is by testing,observation and documentation in the form of a check list. The research process was conductedin two cycles each includes four stages, namely planning, implementation, observation andreflection stages. In the present study showed an increase in activity and student achievement inlearning biology. It can be seen from the increase in the number of students who completed theKKM is ≥75. In the student activity before any action there are 3 students (20%), following thecycle I increased to 7 students (46.6%), the second cycle to 13 students (86.6%) completed. Onstudent achievement also increased the number of students who completed the pre cycle, the firstcycle to the second cycle. Pre cycle 5 students ((33.3%), after the first cycle of action has increasedthere are 8 students (53.3%), the second cycle, there were 13 students (86.6%) completed.Improved completeness KKM students make the mean value the average grade also increasedfrom 54.0 to 70.6 before and increased to 84.3. improvement in cognitive aspects seen from theresults of the post test showed increased learning achievement siswayang biology. Can be seenfrom the increase in the percentage of students completeness, ie the cycle I as much as 53.3% to86.6% in the second cycle. Based on these studies it can be concluded that by using a learningmodel dengann Talking Stick media crossword puzzles can increase the activity of class andstudent achievement VIIE SMP Negeri 1 Kartoharjo.